INFLUENCE OF TEMPERATURE ON THE PERFORMANCE TOOTHED BELTS – BINDER MAGNETIC - Mohammed, Merghache Sidi; El-Amine, Ghernaout Med (European Scientific Journal, ESJ, 2013)
The synchronous transmissions are nearly universal application in all cases where the user wants to have a synchronous operation and without sliding. They are found in diverse areas as micromechanics, office automation, machine tools and industrial shredders. Considering the important role of synchronous belts in the mechanisms functioning, they are the subject of many studies and research in order to the more finely define. In this paper, one trapezoidal tooth profile will be considered with an initial pitch of 10 millimeters an different shapes along width. A test procedure has been defined for temperature measurements. The tests were performed on an original test bench, sensor devices and data acquisition will also be described. Further, results will be synthesized for all synchronous belts in order to make comparisons. Finally, a discussion will allow us to make connections between the influences of design parameters and physical phenomena.